If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 7 = n + -3 Reorder the terms: 7 + 4n = n + -3 Reorder the terms: 7 + 4n = -3 + n Solving 7 + 4n = -3 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 7 + 4n + -1n = -3 + n + -1n Combine like terms: 4n + -1n = 3n 7 + 3n = -3 + n + -1n Combine like terms: n + -1n = 0 7 + 3n = -3 + 0 7 + 3n = -3 Add '-7' to each side of the equation. 7 + -7 + 3n = -3 + -7 Combine like terms: 7 + -7 = 0 0 + 3n = -3 + -7 3n = -3 + -7 Combine like terms: -3 + -7 = -10 3n = -10 Divide each side by '3'. n = -3.333333333 Simplifying n = -3.333333333
| 6x+x=7x | | -41=n+88 | | 15v-14-24=-15 | | -6(b-5)=48 | | 6=10-m | | 3-[4+2(x+3)]=-x+7 | | -x-6-7x+20=-2 | | 2B*10A= | | 15-0.4x=9+0.5 | | 23.4t=24(t-.3) | | 1c(3)=1c+12 | | 36d+15=12 | | 9=7z-13z | | 3A+4C=-13 | | .2(x-25.5)+0.3=-.2(x-16) | | 5+3x=7(x+30) | | z+26=22 | | -4=5X | | 73x-73=711-417 | | 5x^2-20x-14=0 | | 7.49=0.75x+1.39x | | 6y^2-4y+6=0 | | 121x=x+.06x+.15x | | 15y+13(5y-7)=709 | | x^2+3x-0.75=0 | | -13n+13=-12n-9 | | 14(3-10x)-13(10-6x)=98 | | -3.6y+70=-2 | | 4y-1=2y+7 | | c=x+.06x+.15x | | 11=-(3a+1) | | 8(x-3)-3(x-1)=6x+7-5 |